Profiles and spatial distributions of heavy metals, microbial communities, and metal resistance genes in sediments from an urban river - Fu, Lingfang; Yu, Yang; Yu, Fei; Xiao, Jieer; Fang, Huaiyang; Li, Weijie; Xie, Zhijie; Zhang, Feng; Lin, Shu (Frontiers in Microbiology, 2023)
The occurrence and propagation of resistance genes due to exposure to heavy metals (HMs) in rivers is an emerging environmental issue. Little is known about resistance genes in microbial communities in river sediments with low HM concentrations. The profiles and spatial distributions of HMs, the microbial community, and metal resistance genes (MRGs) were analyzed in sediment samples from the Zhilong River basin in Yangjiang city, near the Pearl River Delta. Concentrations of copper (Cu), cadmium (Cd), lead (Pb), chromium (Cr), and nickel (Ni) were relatively low compared with those in other urban river sediments in China. HM chemical composition and fractions and the structure of the microbial community varied along the main channel, but the composition and abundance of MRGs were relatively homogeneous. Variations in HMs and microbial communities in mid- to upstream areas were related to the presence of tributaries, whose inputs were one of the major factors affecting HM chemical fractions and genera structure in mainstream sediments. There were no significant correlations (p < 0.05) between HM concentrations, bacterial communities, and the MRG profiles; thus, HM concentrations were not the main factor affecting MRGs in sediments. These results contribute to understanding the propagation of MRGs in urban rivers in developing cities.